Pengembangan Metode Serbuk Daun Suji (Pleomele angustifolia N.E.Br) sebagai Identifikasi Sidik Jari Laten - Sri Adelila Sari; Desi Heriyanti Nasution (Universitas Andalas, 2021)
Fingerprint is a technology that can be used to identify a person. The dusting method is most often used on latent fingerprints because it is relatively easy and simple. However, the composition of the ingredients used in latent fingerprint powder is toxic and can be hazardous to health. This research was carried out using a new natural powder from Suji leaf as a simple, non-toxic, and cheaper. Suji leaf powder produces a green color that comes from the chlorophyll compounds contained in it. This chlorophyll compound will bind to alanine to identify latent fingerprints. The particle sizes used in this study were of 60-200 mesh. The results found that the particle sizes of 100 and 200 mesh provided good green contrast and clear visualization of the fingerprint patterns. Meanwhile, at the particle size of 60 and 80 mesh, it was found that the results were not clear visualized. The highest percentage of fingerprint patterns based on blood group, gender and ethnicity was found in form of loops. The percentage of fingerprint patterns formed based on the highest was of O 31.1; B 12.2; AB 8.8; and A 6.6 percent. The highest percentage of fingerprint patterns formed by gender were of 45.5 for women and 13.3 percent for men. The highest percentage of fingerprint patterns formed by ethnicity were Malay 21.1, Batak 20, and Javanese 17.7 percent.